2013
DOI: 10.4132/koreanjpathol.2013.47.6.534
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-Associated Protein Tau, α-Tubulin and βIII-Tubulin Expression in Breast Cancer

Abstract: BackgroundThe microtubule-associated protein Tau binds to both inner and outer surfaces of microtubules, leading to tubulin assembly and microtubule stabilization. The aim of this study was to evaluate the significance of Tau, α-tubulin, and βIII-tubulin expression in breast carcinoma and to assess their relationships with disease progression in the context of taxane treatment.MethodsImmunohistochemical expressions of Tau, α-tubulin, and βIII-tubulin were assessed in 183 breast cancer cases. Expression was cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…One of the genes we found to be differentially expressed between SKOV3-NV and SKOV3-C1 (vehicle treated) in our microarray analysis was microtubule associated protein tau ( MAPT ). MAPT , which is associated with paclitaxel resistance in several cancers including EOC [ 22 28 ], was more highly expressed in SKOV3-C1 cells than in SKOV3-NV cells (2.47-fold, p = .00702) (Additional file 2 ). We validated these results by qPCR, finding 4.42-fold higher levels in SKOV3-C1 than SKOV3-NV ( p = .00446) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the genes we found to be differentially expressed between SKOV3-NV and SKOV3-C1 (vehicle treated) in our microarray analysis was microtubule associated protein tau ( MAPT ). MAPT , which is associated with paclitaxel resistance in several cancers including EOC [ 22 28 ], was more highly expressed in SKOV3-C1 cells than in SKOV3-NV cells (2.47-fold, p = .00702) (Additional file 2 ). We validated these results by qPCR, finding 4.42-fold higher levels in SKOV3-C1 than SKOV3-NV ( p = .00446) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the correlation between MAPT and β-tubulin III levels and paclitaxel resistance in gastric cancer [ 23 ], downregulation of MAPT was also shown to improve taxane response in breast cancer cell lines [ 24 ] and in ovarian cancer three-dimensional collagen I matrix culture [ 22 ]. Clinically, expression of the tau protein is associated with worse survival of taxane-treated breast cancer patients [ 28 ]. Since tau proteins are responsible for stabilizing microtubules [ 47 ], higher levels of MAPT could affect the polymerization of microtubules by paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…Stromal myofibroblasts in invasive breast cancer expression of alpha-smooth muscle actin (α-SMA) correlate with worse clinical outcomes [ 25 ] and the metastasis group showed significantly higher α-SMA expression compared with the non-metastasis group. Loss of α-tubulin was significantly correlated with distant metastases [ 26 ]. B2M expression demonstrated a significant difference in the breast cancer molecular subtypes, and may be related to apoptosis regulation in breast cancer [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, a recent study reported that the staining for keratin 18 was weaker in human hepatocellular carcinoma (HCC) than in normal liver tissue 23 . Tubulin families are key components of the cytoskeleton and play important roles in cell metastasis 33 . Some anticancer agents, such as paclitaxel, a promoter of tubulin polymerization, have been found to exhibit clinical activity for metastasis therapy 34 .…”
Section: Discussionmentioning
confidence: 99%